2013
DOI: 10.1016/j.virol.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between claudin-1 and dengue viral prM/M protein for its entry

Abstract: Dengue disease is becoming a huge public health concern around the world as more than one-third of the world's population living in areas at risk of infection. In an effort to assess host factors interacting with dengue virus, we identified claudin-1, a major tight junction component, as an essential cell surface protein for dengue virus entry. When claudin-1 was knocked down in Huh 7.5 cells via shRNA, the amount of dengue virus entering host cells was reduced. Consequently, the progeny virus productions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 74 publications
0
44
0
Order By: Relevance
“…This result, which needs to be investigated further, corroborates the presence of interplay between gypsy and Wolbachia during maternal transmission. Our hypothesis is that Wolbachia could modify gypsy localization at junctions between follicle cells and at the apical domain, as it has previously been shown that bacteria and viruses can interact with junctions between epithelial cells (2830). We therefore propose a model which takes into account previously proposed gypsy and Wolbachia transmission models (8, 9, 13).…”
Section: Discussionmentioning
confidence: 98%
“…This result, which needs to be investigated further, corroborates the presence of interplay between gypsy and Wolbachia during maternal transmission. Our hypothesis is that Wolbachia could modify gypsy localization at junctions between follicle cells and at the apical domain, as it has previously been shown that bacteria and viruses can interact with junctions between epithelial cells (2830). We therefore propose a model which takes into account previously proposed gypsy and Wolbachia transmission models (8, 9, 13).…”
Section: Discussionmentioning
confidence: 98%
“…Claudin-1 expression is upregulated in early stages of DENV infection, which would facilitate virus entry into host cells (Gao et al, 2010;Che, Tang and Li 2013). Some pathogens use tight junction proteins to enter host cells; for instance, it has already been demonstrated that claudin-1 is a co-receptor for HCV entry (Meertens et al, 2008;Liu et al, 2009;Harris et al, 2010).…”
Section: Putative Receptors and Attachment Factors In Mammalian Cellsmentioning
confidence: 99%
“…Some pathogens use tight junction proteins to enter host cells; for instance, it has already been demonstrated that claudin-1 is a co-receptor for HCV entry (Meertens et al, 2008;Liu et al, 2009;Harris et al, 2010). In this context, claudin-1 could function as a co-receptor/receptor for DENV entry, interacting with prMcontaining DENV particles (immature or partially mature particles) and facilitating host cell entry (Gao et al, 2010;Che et al, 2013). Interestingly, claudin-1 expression is decreased in the late stages of infection, which would prevent the entry of a second wave of incoming virus particles, reducing the risk of super-infection.…”
Section: Putative Receptors and Attachment Factors In Mammalian Cellsmentioning
confidence: 99%
“…For example, the tight junction protein occludin has been identified as an essential host factor for entry of several viruses, such as coxsackie B virus (CBV), rotavirus, human hepatitis C virus (HCV), West Nile virus, and others (21,(23)(24)(25). In addition to occludin, the tight junction protein claudin-1 is tightly related to the infection of dengue virus, HCV, West Nile virus, and others (25)(26)(27)(28). During PEDV infection, it has been demonstrated that structural destruction and disorganization of tight junctions are observed (12,29).…”
mentioning
confidence: 99%